Development of working at height management system based on legislation in Malaysia - Law, Peng Hang; Ezrin Hani, Sukadarin (Springer, 2020)
Construction industry is one of the top dangerous industry in Malaysia because there is a high risk of accident occurrence. Amongst of the accidents happen in the construction site, the workers are likely to exposed to the accidents such as fall from height. Although Malaysian government has taken a lot of effort to reduce the number of accidents by legislations, but the construction-related accidents are still at high number especially working at height. Due to concern of this problem, a working at height management system is developed to help the construction especially small medium enterprise contractors to help them to manage the compliance of legal requirements FMA 1976 and OSHA 1994. The legal requirement taken from these two legislations for working at height activity only. The validity of the working at height management system, real case study was used by using a building construction project and interview was conducted with a safety practitioner to validate the working at height legal requirements. As a result, the working at height legal requirements and the prototype were used by a safety practitioner from construction industry to cross-check for compliance and to validate them as well. The developed working at height management system is proven systematically help the end users to store their documentations and check compliance with working at height legal requirements from their inspection checklists. The implementation of this system can contribute to the awareness of complying with the regulations and enhance their safety and health practices.